TOPICAL ASPECTS OF THE RESEARCH OF THE PAST: P. ROSSI’S CONCEPT OF THE CROWD - Dmitry Sergeevich Gorbatov; Anna Vitalyevna Baichik (Sovremennye Issledovaniâ Socialʹnyh Problem, 2018)
The purpose of the study is to identify the main idea of the spontaneous associations concept proposed by Pasquale Rossi, an Italian researcher of the late 19th – early 20th centuries.